Internet connectivity disruption in Sudan (Sudan) - Voidly (2026)
CRITICAL severity disruption detected in Sudan. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: SD-2026-0012
Keywords: internet disruption; SD; disruption; critical